Fertilitätserhalt bei onkologischen Erkrankungen im Kindes- und Jugendalter - Lotz, Laura (Pädiatrische Praxis, 2023)
Prior to the implementation of highly gonadotoxic therapies in children and adolescents, counseling on fertility-preserving measures is now obligatory. The consultation should be interdisciplinary and the individual approach requires an estimation of the expected loss of gonadal function taking into account age, pubertal status, therapeutic regimen and general condition. Since some therapeutic options, especially in prepubertal children, are not yet widely established, these measures should be performed only in centers with sufficient expertise in reproductive medicine.
CRIS-Team Scopus Importer:2024-12-16
Keywords: children gonadotoxicity; cryopreservation; fertility preservation; oncological therapy